Identification of Leptospira interrogans phospholipase C as a novel virulence factor responsible for intracellular free calcium ion elevation during macrophage death. - Jing-Fang Zhao (Public Library of Science (PLoS), 2013)
Background Leptospira-induced macrophage death has been confirmed to play a crucial role in pathogenesis of leptospirosis, a worldwide zoonotic infectious disease. Intracellular free Ca(2+) concentration ([Ca(2+)]i) elevation induced by infection can cause cell death, but [Ca(2+)]i changes and high [Ca(2+)]i-induced death of macrophages due to infection of Leptospira have not been previously reported. Methodology/principal findings We first used a Ca(2+)-specific fluorescence probe to confirm that the infection of L. interrogans strain Lai triggered a significant increase of [Ca(2+)]i in mouse J774A.1 or human THP-1 macrophages. Laser confocal microscopic examination showed that the [Ca(2+)]i elevation was caused by both extracellular Ca(2+) influx through the purinergic receptor, P2X7, and Ca(2+) release from the endoplasmic reticulum, as seen by suppression of [Ca(2+)]i elevation when receptor-gated calcium channels were blocked or P2X7 was depleted. The LB361 gene product of the spirochete exhibited phosphatidylinositol phospholipase C (L-PI-PLC) activity to hydrolyze phosphatidylinositol-4,5-bisphosphate (PIP2) into inositol-1,4,5-trisphosphate (IP3), which in turn induces intracellular Ca(2+) release from endoplasmic reticulum, with the Km of 199 µM and Kcat of 8.566E-5 S(-1). Secretion of L-PI-PLC from the spirochete into supernatants of leptospire-macrophage co-cultures and cytosol of infected macrophages was also observed by Western Blot assay. Lower [Ca(2+)]i elevation was induced by infection with a LB361-deficient leptospiral mutant, whereas transfection of the LB361 gene caused a mild increase in [Ca(2+)]i. Moreover, PI-PLCs (PI-PLC-β3 and PI-PLC-γ1) of the two macrophages were activated by phosphorylation during infection. Flow cytometric detection demonstrated that high [Ca(2+)]i increases induced apoptosis and necrosis of macrophages, while mild [Ca(2+)]i elevation only caused apoptosis. Conclusions/significance This study demonstrated that L. interrogans infection induced [Ca(2+)]i elevation through extracellular Ca(2+) influx and intracellular Ca(2+) release cause macrophage apoptosis and necrosis, and the LB361 gene product was shown to be a novel PI-PLC of L. interrogans responsible for the [Ca(2+)]i elevation.